Assessment of Aflatoxin and Fumonisin Contamination of Maize in Western Kenya - Mutiga, Samuel Kilonzo; Hoffmann, Vivian; Harvey, Jagger J.W.; Milgroom, M.G.; Nelson, R.J. (Scientific Societies, 2015)
We conducted a survey of aflatoxin and fumonisin in maize in western Kenya. In a regional survey of aflatoxin conducted in 2009 across three agroecological zones within three administrative regions, milled maize samples were collected from 985 patrons of 26 hammer mills. Aflatoxin contamination was detected in 49% of samples and was above the regulatory (10 ppb) in 15% of the samples overall; 65% of samples from a drought-prone area were over the limit. In a detailed survey in Bungoma County, we investigated aflatoxin and fumonisin contamination in four popular maize varieties at harvest and after 2 and 4 months of storage. We collected whole-grain samples from farmers’ storage sheds and milled samples from patrons of local mills. Mean aflatoxin contamination was identical for storage sheds and mills at 2.3 ppb. In all, 41% of the samples from mills had detectable aflatoxin, with 4% over the regulatory limit, whereas 87% had detectable fumonisin, with 50% over the regulatory limit (1 ppm). Mean contamination levels did not change during storage. Maize varieties differed in fumonisin contamination, with the most popular varieties vulnerable to both mycotoxins and weevils, which are potential factors in exacerbating mycotoxin contamination. Mycotoxin surveillance is important not just in areas known previously for aflatoxin contamination and acute poisoning but also is needed in all maize-producing regions.